27 Improving end of life care in nursing homes. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Thomson, Magdalen; Killick, Stephanie; McGaughey, Sarah; Platt, Tracey; Gaffney, Rachel
Abstract : Background: There were 716 deaths in Royal Hampshire County Hospital and Andover Ward Memorial hospitals (including hospice) in 2016. With no hospice beds in Winchester 25% patients die in a care home opposed to 18% nationally. The team felt that the quality of care homes was variable, staff lack confidence and competence, symptom were not always well controlled, and lack of advanced care planning resulted in inappropriate hospital admissions. Method: One year quality improvement project carried out by a cross –organisational team including a commissioner, a community pharmacist, two care home managers, a specialist palliative care team Consultant, and two palliative care clinical matrons from acute hospital and hospice. The project was supported by NHS Wessex. The PDSA cycle used mapping of existing discharge processes, stakeholder analysis, a driver diagram, and a risk chart. Quantitative and qualitative interview data was collected. Changes were implemented at regular intervals throughout the year and education was provided. Initial syringe driver usage was also measured. Quantitative results: Each care home rating out of 10 rose from 7.6 and 8.6, to 9.5 and 9.6 respectively. One received an 'outstanding' CQC rating for end of life care. 3 core qualitative questions were asked to measure confidence and competence. At the start of the project 67% responded positively, which rose to 100% by the end. Staff and family feedback was overwhelmingly positive and there were no inappropriate hospital admissions. There were several unintended benefits including better inter-rational working for between hospital and care homes, increased levels of trust, better quality of information, and staff felt empowered to influence care provided by GPs. Conclusion: The study showed that this had been a successful project with several additional unintended benefits. The team are planning to replicate the project in further care homes and fund raising is well underway to open Winchester hospice next year (2019).